(untitled) (LEARNing Landscapes, 2008)
This paper presents a palimpsest of ways in which self-study draws upon arts-based methods not just as processes towards teacher development, but also as means to problematize and inquire into conceptualizations of the self. It focuses on the creation of individual self-boxes that mediate teachers’ dynamic narratives of identity. Concepts of the unitary self, the decentred self and the relationship between inner and outer experience are challenged and illustrated through two interlapping stories made manifest through the creation of self-boxes.